FAKTOR RISIKO BERAT BAYI LAHIR RENDAH (BBLR) PADA BAYI BARU LAHIRDI RSUD BANJARNEGARATAHUN 2011 - Etika Dewi Cahyaningrum; Wirantika Dwi Nency (Viva Medika, 2012)
Background: Each year the world's estimated birth about 20 million or 27% ofdeaths due to low birth weight neonates. Factors causing LBW from maternalfactors, fetal factors and environmental factors. LBW births partly caused bypremature birth, and partly because of impaired growth during pregnancy. Objective: To identify risk factors for LBW picture on BBL Banjarnegara DistrictHospital in 2011. Methods: This research method is descriptive survey based on primary data andsecondary data were taken using a live interview at the hospital in 2011Banjarnegara in 12-25 June 2011. Results: The majority of babies born at low birth weight category largely on theparity of more than 4 by 66.7%, the gestational age preterm/dismatur respectively88.2% and 100%. With anemia/preeclampsia respectively 58.3% and 62.5%.Experienced weight gain of less than 9 kg of 70%. Gemeli baby at 66.7%. Conclusion: Compared with children born with BBLN, the risk factors of infantsborn with low birth weight was greater in mothers with parity more than 4, with agestational age preterm/dismatur, with anemia/preeclampsia, experience weightgain of less than 9 kg, and birth gemeli baby. Keywords: Risk factors for LBW, Newborn